Peningkatan kemampuan berpikir prosedural dan numerik dalam statistika melalui integrasi nilai-nilai keislaman - Sari, Dewi Purnama; Mulyana, Ahmad Nana Mahmur; Rusli, Rachmatullah; Feriani, Dwi; Septian, Yandra Ega; Karmila, Karmila (Penamas: Journal of Community Service, 2025)
The objective of this Community Service activity is to improve the understanding of students of SMAN 6 South Tangerang City of the basic concepts of statistics through an integrative approach with Islamic religious values. This approach is focused on strengthening students’ procedural and numerical thinking skills in solving statistical problems. The methods used in this activity include interactive lectures, group discussions, and problem exercises contextualized with Islamic spiritual values. The activity results showed that most students could understand the steps of solving statistical problems procedurally and experienced an increase in connecting statistical symbols and concepts with their experiences and religious values. The participants’ enthusiasm during the activity also reflected the effectiveness of this value-based approach in strengthening students’ thinking and numeracy skills.